Strategy for Mobility - Owen, Wilfred (Washington : Brookings Institution, Transport Research Program, 1964)
Since accessibility and mobility are involved in almost everything that developing countries are striving to accomplish, the book attempts to look at transport in relation to the total environment. The work is thus designed to help guide the allocation of resources in emerging economies and in foreign assistance programs, to shed light on the possibilities that science and technology offer for the solution of transport problems etc.
Bibliography: p. 229-236.
ne 21/02/2018
Loan
Keywords: Transportation; Economic Development; Developing Countries